Water-vapor foreign-continuum absorption in the 8–12 and 3–5 μm atmospheric windows. (August 2015) - Klimeshina, T.E.; Rodimova, O.B.
Abstract: The frequency and temperature dependence of the water vapor–nitrogen continuum in the 8–12 and 3–5 μm spectral regions obtained experimentally by CAVIAR and NIST is described with the use of the line contour constructed on the basis of asymptotic line shape theory. The parameters of the theory found from fitting the calculated values of the absorption coefficient to the pertinent experimental data enter into the expression for the classical potential describing the center-of-mass motion of interacting molecules and into the expression for the quantum potential of two interacting molecules. The frequency behavior of the line wing contours appears to depend on the band the lines of which make a major contribution to the absorption in a given spectral interval. The absorption coefficients in the wings of the band in question calculated with the line contours obtained for other bands are outside of experimental errors. The distinction in the line wing behavior may be explained by the difference in the quantum energies of molecules interacting in different vibrational states. Highlights: We consider water vapor continuum absorption as a monomer line wing absorption. Asymptotic line wing theory includes classical and quantum interaction potentials. Potential parameters of line wing shape are found from comparison with experiment. Line wing shape obtained describes spectral dependence of the H2 O–N2 continuum. The same procedure describes spectral dependence of the H2 O–N2 absorption in 8–12 and 3–5 μm windows.